Uncertainties Experienced by Suppliers Participating in Customers' Product Development Projects - Flankegård, Filip; Johansson, Glenn (International Conference NordDesign 2024, Reykjavik, Iceland, 2024-08-12 - 2024-08-14, 2024)
This paper explores uncertainties experienced by suppliers involved in their customers' product development projects. The study introduces a model for classifying different types of involvement, which is used to identify uncertainties and effects across the various types. Empirical data originates from a multiple case study involving four SME suppliers. Four types of uncertainty are identified. These uncertainties stem from both customer and supplier organizations as well as from technology.
Keywords: Case Study; NPD; SME; Supplier Collaboration; Supplier Integration